COMP: a candidate molecule in the pathogenesis of systemic sclerosis with a potential as a disease marker. Issue 9 (7th December 2007) - Hesselstrand, R; Kassner, A; Heinegård, D; Saxne, T
Abstract : Objective: Cartilage oligomeric matrix protein (COMP), primarily found in cartilage, is thought to be an important regulator of assembly and maintenance of the fibrillar collagen I and II networks. Recently, COMP was shown to be produced by skin fibroblasts from patients with systemic sclerosis (SSc, or scleroderma). The purpose of this study was to examine whether COMP is released from skin to serum in patients with SSc, and may serve as indicator of activity of skin involvement. Methods: Serum COMP levels were measured by enzyme linked immunosorbent assay in patients with SSc whose skin involvement was assessed with the modified Rodnan skin score (mRss) and high frequency ultrasound. The presence of COMP in skin biopsies was assessed by Western blot using a monoclonal antibody specific for the very C-terminal end of human COMP. Results: Serum COMP correlated to skin involvement as measured by the mRss (n = 70; rS = 0.60; p<0.001), to skin thickness measured by ultrasound (n = 88; rS = 0.55; p<0.001) and inversely to skin echogenicity measured by ultrasound (n = 88; rS = −0.40; p<0.001). In 70 patients followed longitudinally there was a correlation between changes in serum COMP (n = 307) and changes in mRss (rS = 0.35; p = 0.008). In individual patients monitored with repeated measurements, serum COMP changes closely paralleled changes in mRss. A C-terminal COMP fragment, with an apparent molecular mass of 56 kDa, was identified in SSc skin biopsies, while no COMP reactivity was detected in normal skin. Conclusion: The high turnover of COMP in SSc skin suggests a pathophysiological role. Serum COMP shows promise as a new biomarker in SSc.